2013
DOI: 10.1111/1346-8138.12353
|View full text |Cite
|
Sign up to set email alerts
|

Drug survival rates in patients with psoriasis after treatment with biologics

Abstract: Clinically, patients' adherence to biologic treatment is not only related to efficacy but also to adverse events, cost and other factors. To evaluate long-term viability of biologic treatment, both the percentage of and reasons for discontinuation of treatment were investigated. In this study, patients treated with infliximab (n = 38), adalimumab (n = 59) and ustekinumab (n = 30) were included and observed for 12 months. Clinical efficacy was evaluated using a 75% reduction of Psoriasis Area and Severity Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
2
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 12 publications
8
67
2
11
Order By: Relevance
“…Thirteen observational studies with 17,444 patients reported on the comparative risk of discontinuation of TIMs due to AEs (see Supplementary Table 1, available Six observational studies reported only crude rates of discontinuation and did not provide comparative estimates (22)(23)(24)(25)(26)(27). These studies generally observed a higher proportion of patients discontinuing infliximab than adalimumab, etanercept, or anakinra treatment due to AEs in CD, RA, and plaque psoriasis.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen observational studies with 17,444 patients reported on the comparative risk of discontinuation of TIMs due to AEs (see Supplementary Table 1, available Six observational studies reported only crude rates of discontinuation and did not provide comparative estimates (22)(23)(24)(25)(26)(27). These studies generally observed a higher proportion of patients discontinuing infliximab than adalimumab, etanercept, or anakinra treatment due to AEs in CD, RA, and plaque psoriasis.…”
Section: Resultsmentioning
confidence: 99%
“…Three of these studies have only reported on drug survival with TNFIs (Brunasso et al, 2012;Esposito et al, 2013;Gniadecki et al, 2011), while two involved the same Danish national psoriasis biologic safety registry data DERMBIO (Gniadecki et al, 2014;Gniadecki et al, 2011), with the other centres reporting data from either a single or a limited number of centres (Menting et al, 2014;Umezawa et al, 2013;van den Reek et al, 2014c). The…”
Section: Introductionmentioning
confidence: 99%
“…Clinical outcomes (mainly PASI) were reported in 75% of prospective studies [27, 39, 47-53], in about 50% of prospective registries [20, 24, 54-61] and retrospective studies [29, 30, 32, 34, 37, 62-70], and in no retrospective administrative databases/claims. Drug survival of biological therapies was reported in over 60% of prospective registries [14, 20, 21, 24, 25, 31, 54, 57, 71-74], retrospective studies [18, 19, 22, 23, 26, 29, 30, 32, 34, 37, 38, 68, 70, 75-77] and administrative databases/claims [28, 35, 36, 40-42, 46], and less frequently (33%) in prospective studies [27, 33, 52, 78]. Subanalyses on reasons of discontinuation, such as switching, dose augmentation, or biological therapy restarting, were scanty.…”
Section: Resultsmentioning
confidence: 99%